Aspidistra congestiflora (Asparagaceae, Convallarioideae), a new species from central Laos - Averyanov, Leonid V.; Vislobokov, Nikolay A.; Nuraliev, Maxim S.; Maisak, Tatiana V.; Krupkina, Ludmila I.; Doan, Nga Thi (Phytotaxa, 2025)
Aspidistra congestiflora discovered in a karstic limestone area in central Laos (Vientiane Province, Vang Vieng District) is described and illustrated as a species new to science. It is characterized by obconoid perianth tube, triangular perianth lobes without appendages, and widely obconoid pistil with prominent longitudinal ridges. The new species is morphologically most close to A. zhangii, from which it differs in longer petioles and purple-violet flowers. In addition, A. congestiflora is similar to A. leucographa, A. longhuiensis, A. opaca, and A. papillata in the general flower appearance, but readily differs from these four species in obconoid pistil. Aspidistra congestiflora is also similar to A. obtusata in the shape of flower (including obconoid pistil), as well as in its general appearance, but differs in often finely verruculose perianth lobes, larger pistil with longitudinal ridges, and purple-violet stigma. The newly discovered species is expected to be a local endemic and will probably need protection in the near future.